(untitled) (Ameghiniana, 2016)
Since its original description nearly two hundred years ago, the late Pleistocene (Ensenadan–Lujanian SALMA) ground sloth genus Mylodon from South America has had a variety of taxonomic issues. The end result is that diagnostic characters for the genus and its only species, M. darwinii, include only skull, tibia, and astragalus features. While other postcranial remains have been found, they have been too fragmentary to provide any significant taxonomic characters. The rediscovery of a specimen of M. darwinii (previously listed as Glossotherium robustum) collected in the mid-1920s near Orient in Buenos Aires Province, Argentina and housed in the Field Museum of Natural History, provides an opportunity to expand the diagnosis for this taxon based on diagnostic skull and astragalus remains that are associated with an atlas and associated vertebrae, and most of the left forearm, carpus, and other elements of the manus. These bones all show features that distinguish M. darwinii from contemporaneous mylodontids (e.g., Catonyx, Glossotherium, Lestodon, Scelidotherium), as well as some simple differences in size. The suite of currently known morphological characters and reconstructed muscle attachments also indicate a general functional niche for M. darwinii. They suggest that its body weight was borne on the lateral side of the manus rather than the knuckles or unguals, and that Mylodon may have had a relatively high degree of manual dexterity or digital strength. Resumen. DESCRIPCIÓN DE ELEMENTOS POSTCRANEALES NUEVOS DE MYLODON DARWINII OWEN 1839 (MAMMALIA: PILOSA: MYLODONTINAE), Y LA MORFOLOGÍA FUNCIONAL DEL MIEMBRO ANTERIOR. Desde su descripción original hace casi doscientos años, el género de perezoso terrestre Mylodon del Pleistoceno tardío de América del Sur (Edad-mamífero Ensenadense–Lujanense) ha tenido muchos problemas taxonómicos. El resultado final es que los caracteres diagnósticos del género y su única especie, M. darwinii, solo incluyen rasgos del cráneo, tibia, y astrágalo. A pesar de que han sido encontrados otros restos postcraneales, éstos han sido demasiados fragmentarios para proporcionar algunos caracteres taxonómicos significativos. El redescubrimiento de un ejemplar de M. darwinii (anteriormente identificado como Glossotherium robustum) recolectado a medianos de la década 1920 cerca de Oriente en la provincia de Buenos Aires, Argentina y guardado en Field Museum of Natural History, proporciona una oportunidad de ampliar la diagnosis de este taxón sobre la base de restos diagnósticos del cráneo y astrá- galo asociados con un atlas y vértebras asociadas, la mayor parte del miembro anterior izquierdo, carpo, y otros elementos de la mano. Todos estos huesos muestran rasgos que distinguen M. darwinii de milodóntidos contemporáneos (e.g., Catonyx, Glossotherium, Lestodon, Scelidotherium) además se algunas diferencias sencillas en el tamaño. El conjunto de caracteres morfológicos actualmente conocidos y áreas reconstruidas de origen e inserción de músculos también indican un nicho funcional para M. darwinii. Sugieren que el peso corporal fue soportado por el lado exterior de la mano en vez de las articulaciones de los dedos o las falanges ungueales, y que Mylodon podría haber tenido un grado de flexibilidad manual o fuerza digital relativamente alto.